Galactic star formation with NIKA2 (GASTON): Filament convergence and its link to star formation - Peretto N.; Adam R.; Ade P.; Ajeddig H.; André P.; Artis E.; Aussel H.; Bacmann A.; Beelen A.; Benoît A.; Berta S.; Bing L.; et al. (EPJ Web of Conferences, 2022)
In the past decade filaments have been recognised as a major structural element of the interstellar medium, the densest of these filaments hosting the formation of most stars. In some star-forming molecular clouds converging networks of filaments, also known as hub filament systems, can be found. These hubs are believed to be preferentially associated to massive star formation. As of today, there are no metrics that allow the systematic quantification of a filament network convergence. Here, we used the IRAM 30m NIKA2 observations of the Galactic plane from the GASTON large programme to systematically identify filaments and produce a filament convergence parameter map. We use such a map to show that: i. hub filaments represent a small fraction of the global filament population; ii. hubs host, in proportion, more massive and more luminous compact sources that non-hubs; iii. hub-hosting clumps are more evolved that non-hubs; iv. no discontinuities are observed in the properties of compact sources as a function of convergence parameter. We propose that the rapid global collapse of clumps is responsible for (re)organising filament networks into hubs and, in parallel, enhancing the mass growth of compact sources.